Income taxation and household size: would French family splitting make German families better off? - Alexandre Baclet; Fabien Dell; Katharina Wrohlich (Institute for the Study of Labor (IZA), 2005)
In this paper, we address the question whether family support via the income tax system is more generous in France than in Germany, as it is often claimed in the public debate. We use two micro-data sets and a micro-simulation model to compare effective average tax rates for different household types in France and Germany. Our analysis shows that the popular belief that French high income families with children face lower average tax rates than their German counterparts is true, however not due to the French Family splitting but rather to the different definitions of taxable incomes in both countries. Actually, low income families with less than three children even fare better in terms of tax relief in Germany than in France. The French system leads to lower average tax rates than the German one (over a large range of the income distribution) only for families with three children.
Keywords: D31; H24; J18; 330; income taxation; family; income distribution; France; Germany